A Literature Based Study on the Effectiveness of Neuromuscular Electrical Stimulation (NMES) on Quadriceps Strength And Knee Function or Movement following ACL Reconstruction of the Knee: Examining the Effectiveness of NMES on Quadriceps Strength and Knee Function post ACL Reconstruction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Anterior cruciate ligament (ACL) reconstruction affects both muscle strength and function of the knee. Standard rehabilitation protocols include strengthening of the muscles through voluntary exercise. Earlier studies have suggested that NMES could enhance muscle strength. However, there are varying evidences on the effectiveness of NMES in improving muscle strength or knee movement and function. The main aims of this study are to review findings from studies on the 1. effectiveness of NMES in improving quadriceps strength following reconstruction of ACL rupture 2. effectiveness of NMES in improving knee movement or function following reconstruction of ACL rupture.Method A literature-based study design was chosen to address the aims of this study. Ten studies were retrieved and reviewed using critical appraisal skills programme (CASP) tools and the physiotherapy evidence base (PEDro) scale.Result Studies revealed that the effects of NMES on quadriceps strength were moderate. Few of the studies which included knee movement or function as a patient outcome reported improvements in the movement of the knee. The small sample sizes of most of the RCTs compromised the applicability of the findings to a larger and more heterogeneous population. There was also variation in the parameters used in NMES application. This could also account for the differences of the effects of the intervention on both quadriceps strength and knee movement or function. The reviewed studies also did not follow-up the patients in the long term. It is not clear whether the effects of NMES are sustained over time.Conclusion Neuromuscular electrical stimulation could yield moderate improvements on quadriceps strength and knee movement or function. It is recommended that future studies should employ large sample sizes to reduce bias in the findings of the study. It is also recommended that follow-up will be conducted in the long term to determine the long-term effects of this intervention.